BIMBINGAN PENERAPAN PRODUCT VISUAL GUNA MENDUKUNG PEMASARAN ONLINE PADA USAHA BAWANG GORENG UMKM MAHASISWA MLG - Rena Feri Wijayanti; Lina Budiarti; Tri Yulistyawati Evelina; Erlangga Andi Sukma; Sanita Dhakirah (Jurnal Pengabdian kepada Masyarakat, 2025)
The various products offered by online-based businesses certainly bring challenges to catch consumers' attention. Understanding the importance of a product's appearance (product visual) in high competition opens the eyes of businessmen who want to get involved in online businesses that require thorough preparation, one of which is the aspect of the product's visual appearance displayed on the online platform used. One of the main focuses of this community service is aligned with the needs of partners is to develop the market by trying to expand through the marketplace, so the service team maximizes resources and efforts to be able to help maximize the application of product visuals to strengthen the products offered in the online platform so they can attract the attention of online shopping lovers to look for further product information from the existence of aesthetic product images. The method used in this community service activity is assistance starting from determining the appropriate concept, selecting product variants that are superior products, and consulting with photography experts to get product photos that contain photography/aesthetics aspects. The result of this community service is some photos of the product that are ready to be uploaded on a social media or marketplace platform.